Strengthening the Strategic Role of Mosques in Jakarta: From Spiritual Preaching to Economic Empowerment - Hamid, Abdul; Uyuni , Badrah; Anim , Sarbini; Ahmad, Mohamad Shodiq; Muslimin , Muslimin; Fahrany, Sofia (MADINAH, 2025)
Mosques, as the center of worship for Muslims, play a strategic role in the formation of an empowered society. However, in the context of Jakarta as an urban city, the role of mosques in the economic empowerment of the people is still not optimal. This research aims to explore and analyze the role of mosques in revitalizing da'wah, which includes spiritual aspects and economic empowerment of the people. Using a qualitative approach and case study method, this study examines several mosques in Jakarta that have implemented various da'wah-based economic empowerment programs, such as mosque cooperatives, entrepreneurship training, and other social programs. Data were obtained through in-depth interviews, participatory observations, and documentation analysis. The study results show that although some mosques have successfully implemented economic empowerment programs, there are challenges in integrating da'wah aspects with economic empowerment. The main obstacles include limited resources, lack of coordination between institutions, and shifting da'wah focus. This study recommends a revitalization strategy to strengthen the role of mosques in the economic empowerment of the ummah through the synergy between da'wah, education, and community-based economic empowerment. It is hoped that the results of this research can contribute to optimizing the function of mosques as da'wah centers that are integrated with economic empowerment in urban communities